Duration of Gadget Usage Affects Eye Fatigue in Students Aged 16-18 Years - Nafolion Nur Rahmat; Al Munawir; Saiful Bukhori (Humanistic Network for Science and Technology (HNST), 2017)
Gadget is one of the innovations generated by humans in order to simplify the work or for the benefit of everyday because with gadgets will easily get various kinds of information needed with a single press. Gadgets easily accessible by everyone one of them is a student or schoolchild so that it is possible for school children have complaints on the eyes if too concentrated on gadgets. Student should know Factors associated with vision complaints such as gender and length of use of gadgets in a day. The purpose of this study was to determine the effect of long use of gadgets against eye fatigue. This research is analytic observational with cross sectional method. The population in this study were all students in SMA Zainul Hasan Gengong Problinggo which used gadgets as many as 296 students. A large sample calculation using the formula Isaac and Michael, amount to 165 students. Sampling technique with simple random sampling and carried out in August 2017. To determine the effect of the long use of gadgets against eye fatigue is used chi-Square test. The results of this study as many as 58 respondents who long using gadgets and fatigue, 22 respondents used gadget for < 2 hours, 3 respondents used gadget 2-3 hours, 5 respondents used gadgets for >3-4 hours, 4 respondents used gadget for > 4-6 hours, 23 respondents usedgadget for >6-8 hours, and 1 respondents used gadget > 8 hours. then. Respondents who long used gadget and did not experience some eye fatigue 107 respondents, 43 respondents used gadget for < 2 hours, 30 respondents used gadget 2-3 hours, 20 respondents used gadget for > 3-4 hours, 3 respondents used gadget for > 4-6 hours, 9 respondents used gadget for >6-8 hours, and 2 respondents used gadget > 8 hours. ChiSquare result is taken data P value < 0,00 with α significance 0,05 so it takes conlusion H1 received if P value <0,05 it means there is an effect of long time usage of gadget against eye fatigue in SMA 1 Zainul Hasan Genggong Probolinggo. Technological innovation is made in the purpose in order to simplify all human affairs hence from the human unknowingly also exposed negative impact of the use of gadgets one of them is eyestrain Keywords: Duration, Gadget usage, Eye fatigue